Conhecer para ensinar: as narrativas de Daniel Parish Kidder sobre o Brasil sob a perspectiva da educação cristã - Costa, Eber Borges da (2022)
This research analyzes the narratives of Christian missionary and educator Daniel Parish Kidder (1815-1891) who was in Brazil in the first half of the 19th century and registered his impressions about the country, its people and its institutions. The work starts from the hypothesis that there is a very particular understanding of Christian education in their narratives, which is motivated by the desire to know the other. In this movement of knowing to teach, it produces reports that contribute to a better understanding of the relationship between education and religion in Brazil and to an understanding of Christian education and its impacts on society. Christian education is approached from a Protestant perspective, in an interdisciplinary work that brings to the field of Education an expression of the area of Science of Religion and of Theology. Christian religious communities are considered to be important spaces of non-formal education in which worldviews, concepts and prejudices are formed. The foundational events of the educational practice of Christian churches in Brazil, such as Jesuit education and Protestant education, are used to contextualize Kidder's performance and his narratives. The objective of the research is to analyze these narratives in search of his vision of Christian education, with its extent and limitations, and how he approaches another culture in the movement from knowing to teaching. Implicitly, he asks the question about where he works and about the people he intends to teach. This is a qualitative research based on Narrative Research and bibliographical research on Christian education in Brazil, highlighting the close relationship between education and religion, while problematizing this relationship. The key to reading these narratives is the Culture Circle, systematized by Freire, and the themes that emerge from them are discussed in dialogue with current themes. As a result of reading and analyzing Kidder's narratives, a necessary redefinition of Christian education in the dimension of dialogue and care emerged; a Christian education that, like Kidder, asks the question for the world and the people it intends to teach. Answering it involves considering the ambiguities and tensions that characterize both Christian education as the world and the people who inhabit and build it.(AU)